IMPLEMENTASI PROGRAM KAMPUS MENGAJAR 7 DALAM MENINGKATKAN LITERASI DAN NUMERASI SISWA SMP NEGERI 43 MERANGIN - Nurleni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Kampus Mengajar 7 Program is part of the Merdeka Belajar Kampus Merdeka policy, which aims to improve the quality of education, particularly in the aspects of literacy and numeracy. This study aims to describe the implementation of the Kampus Mengajar 7 Program in improving students' literacy and numeracy skills at SMP Negeri 43 Merangin. The research method used is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation.The results show that the implementation of the program is carried out through various activities, such as assisting classroom learning, fostering literacy habits through reading activities, and strengthening numeracy through practice exercises and innovative learning media. This program has a positive impact on improving students' reading skills, text comprehension, and arithmetic abilities. In addition, the involvement of university students increases students’ learning motivation and helps teachers create more varied and interactive learning environments. The program also contributes to the improvement of students’ literacy skills, as indicated by increased reading fluency, better comprehension of texts, and higher reading interest. In terms of numeracy, students show improvement in understanding basic mathematical concepts and solving arithmetic problems. Therefore, the Kampus Mengajar 7 Program has proven to be effective in supporting the enhancement of students' literacy and numeracy skills at SMP Negeri 43 Merangin.